Manajemen Pengembangan Masyarakat: Penguatan Perilaku Filantropi pada Masyarakat Kampung Mualaf Temanggung - Imam Subqi; Sutrisno Sutrisno (Empower : Jurnal Pengembangan Masyarakat Islam, 2023)
The convert village of Dusun Batursari, which has great potential in various fields, but has not been able to work on it optimally, is a strategic opportunity. The purpose of this study was to explore management, supporting and inhibiting factors for community development through strengthening philanthropic behavior in the convert village of Temanggung by using qualitative research. The results of this study indicate that: (1) there are six stages in community development through philanthropy, namely: preparing plans such as routine recitation, program implementation, reflection, and evaluation. (2) the supporting factors are human resources and leadership while the inhibiting factors are lack of information. The contribution of this research can be used as a reference for conducting philanthropic-based community development. rejekibet apkjaya slotokjktslot totokm777 apkdan777 apkrejekibet apkjayaslot loginslotslot pulsadownload apk rejekibetpc777 login apkkm777 apkdan777 apkaplikasi 55kbet